Enterococcus raffinosus, Enterococcus durans and Enterococcus avium Isolated from a Tertiary Care Hospital in Romania—Retrospective Study and Brief Review - Dan Alexandru Toc; Stanca Lucia Pandrea; Alexandru Botan; Razvan Marian Mihaila; Carmen Anca Costache; Ioana Alina Colosi; Lia Monica Junie (Biology, 2022)
(1) Background: This paper aims to provide a description of non-faecalis non-faecium enterococci isolated from a tertiary care hospital in Romania and to briefly review the existing literature regarding the involvement of Enterococcus raffinosus, Enterococcus durans and Enterococcus avium in human infections and their antimicrobial resistance patterns; (2) Methods: We retrospectively analyzed all Enteroccocus species isolated from the “Prof. Dr. O. Fodor” Regional Institute of Gastroenterology and Hepatology from Cluj-Napoca during one year focusing on non-faecalis non-faecium Enterococci. A brief review of the literature was performed using case reports involving Enterococcus raffinosus, Enterococcus durans and Enterococcus avium; (3) Results: Only 58 out of 658 Enteroccocus isolates were non-faecalis non-faecium and met the inclusion criteria. These species were isolated more often (p < 0.05) from the surgical ward from mixed etiology infections with E. coli. In our review, we included 39 case reports involving E. raffinosus, E. durans and E. avium; (4) Conclusions: Isolation of non-faecalis non-faecium enterococci displays an emerging trend with crucial healthcare consequences. Based on the analysis of the case reports, E. avium seems to be involved more often in neurological infections, E. durans in endocarditis, while E. raffinosus displays a more heterogenous distribution.